Ritoj bus geriau - Juozapaviciute, Monika (Lithuania, 2003)
The stories of four women from different sectors of society are woven together to make a collective portrait of Lithuanian women, who have had to adapt to radically new conditions since transition. An unemployed actress fights against depression after losing her beloved work. A resilient saleswoman will try anything from selling items purchased abroad to running a dating service. A woman farmer courageously tries to keep her farm afloat. A political scientist from Vilnus is apparently the only one who had no trouble making the transition from being a part of the Soviet elite to being a part of the elite of an independent Lithuania. This film is part of the Gender Montage: Paradigms in Post Soviet Space film series made by The Network Women's Program of the Open Society Institute - Russia and the Gender Policy Institute.
Keywords: Documentary films